Worlds of illness : biographical and cultural perspectives on health and disease - Radley, Alan, 1946- (Routledge, 1993)
In recent years the study of illness as experienced by patients has emerged as an approach to understanding sickness. Descriptions of the everyday situations of people with particular diseases, provide a commentary upon the nature of symptoms and upon the relation of the body to society. This approach stresses the biographical and cultural contexts in which illness arises and is borne by individuals and those who care for them. It emphasises the need to understand illness in terms of the patients own interpretation, of its onset, the course of its progress and the potential of the treatment for the condition. Worlds of Illness examines people's experience of illness and their understanding of what it means to be healthy. The contributors are the first to offer this biographic and cultural approach in one volume, redefining the perspective further and drawing attention to its potential for questioning theoretical assumptions about health and illness.